Population recovery and fertility Among the Kamaiurá, Tupi people of the Alto Xingu, Central Brazil, 1970-2003 - Pagliaro, Heloisa; Junqueira, Carmen (Saúde e Sociedade, 2007)
This paper analyses the fertility of the Kamaiurá, a Tupi people that inhabits the Xingu Indigenous Park (XIP), between 1970 and 2003. Data has been gathered from medical records of the Health Program of the São Paulo Federal University (Unifesp) at XIP, and from a survey conducted at the Kamaiurá village in 2003. Results have shown that before 1966, high mortality rates due to disputes among the indigenous nations of the region and contagious diseases, as well as moderate fertility levels were responsible for the stability trend of the population. The average population growth between 1967 and 2003 was 3.5%. Total fertility rates increased from 5.7 to 6.2 births per woman, between 1970 and 2003, reaching their highest level in 1980 (6.6). Since the 1990s there has been an ageing of the reproductive patterns, with the decrease of fertility levels among women up to 24 years of age, and an increase among women in the other age groups. The average age at first birth increased from 16.2 to 18.8 years between 1970-2003; the proportion of single women older than 15 years also increased: from 6.3% in 1971 to 26% in 2003; the inter-birth intervals varied between 30.3 and 36 months. The increase in the Kamaiurá's fertility rate was favored by the decrease in general and infant mortality rates, but the Kamaiurá did not abandon their traditional fertility controls, which has allowed a rational and balanced population growth.